Republic of India : Mutisectoral Nutrition Action in Bihar - Kathuria, Ashi Kohli (World Bank, Washington, DC, 2014)
India, currently, has one of the highest malnutrition rates in the world. One-third of its children are born with low birth-weight, 43 percent of children under five are underweight, 48 percent are stunted and 20 percent are wasted. Stunting rates in India are two to seven folds higher than those of other BRICS countries. Micronutrient deficiencies are extremely high with almost 75 percent of the under threes being anemic, 62 percent deficient in vitamin A and over 13 million infants remaining unprotected from iodine deficiency disorders. There are large differentials in the prevalence across states and socio economic groups. Sixty percent of the malnutrition burden exists in low income states: Bihar, Chhattisgarh, Jharkhand, Madhya Pradesh, Odisha, Rajasthan and Uttar Pradesh. The Government's policy commitment to address malnutrition and the multitude of programs that are being implemented, progress in reducing under nutrition has been slow. It therefore becomes imperative to address the malnutrition challenge and to prevent and reduce maternal and child malnutrition as early as possible across the life cycle especially through pregnancy and in the first two years of life, i.e., in the first 1,000 days of life, and in adolescent girls and women. In order to accelerate improvements across the states, the Government of India (GOI) has made policy commitments to mobilize multisectoral action to address the multiple causes of malnutrition effectively through formulating a multisectoral strategy and a multisectoral program to be implemented in 200 high malnutrition burden districts of the country. The multisectoral strategy also aims to bring a strong nutrition focus in various sectoral plans to address maternal and child malnutrition.